Role of non governmental organisations (NGOs) in empowerment of farmers - Jyothish Mannambeth (Department of Agricultural Extension, College of Agriculture, 2000)
Developmental programmes implemented through government machinery could not bring about much changes in the rural sector as far as the developmental aspects are concerned. At the same time, many of the NGOs working in the rural areas could bring about attractive results. So a study was undertaken to identify the dimensions of empowerment of farmers through NGOs, to study the roles played by NGOs, to study the extent of people participation and to develop a strategy for empowerment of farmers. Kannur district was selected as the locale of study and ten functional NGOs were randomly selected. From each NGO, ten beneficiaries and ten non beneficiaries were selected as respondents. Data was collected using structured pre tested interview schedule. Nineteen variables were selected for the study and from that fourteen variables identifies as dimensions of empowerment. The beneficiaries were found better compared to non beneficiaries in almost all the variables studied. The perception about the role of NGOs were more with the beneficiaries than non beneficiaries. Extent of participation in. the various activities were also more with beneficiary farmers. Lack of evaluation, Non co-operation from the government side and lack of financial support and lack of follow up were the main constraints faced by •NGOs. The steps for strengthening NGOs include effort from government side, training of staff, constant touch with academic institutes properly documented programmes, coordination between NGOs and experimenting with new ideas. Strategy for empwerment of farmers aims at collection of data, assessing needs, creating awareness, establishing rapport, identification of resources, organising people in subgroups, defining goals and achieving objectives.